ESENSI DAN PROSES PEMBUKTIAN EKUIVALENSI LOGIS MENGGUNAKAN SIMBOL LINGKARAN PUTIH DAN LINGKARAN HITAM - Tampubolon, Junius Karel; Santosa, Raden Gunawan (Program Studi Pendidikan Matematika, 2025)
The essence of the equivalence of P and Q is a condition that shows that P and Q have the same meaning based on the established reference. Achieving equivalence between P and Q involves transforming the form of P into Q while consistently obeying the established reference. The process of transforming P into Q using the symbols white circle and black circle while maintaining their equivalence is known as the equivalence step. The essence of logical equivalence steps are simplification, substitution and construction. The purpose of this study is to explore the process of the equivalence step more deeply to simplify the expression of propositions and ensure that the meaning of the symbols remains consistent and does not change the meaning of its original context after the equivalence step is carried out. The method used in this study has four stages, namely the preparation of equivalence guidelines, the development of problem-solving questions, simulation experiments, and the last is error evaluation. This study concludes that errors in the equivalence step often occur due to misunderstandings in the use of logical relationships such as